Regionalization of water quality parameters based on the landscape characteristics of small ungauged basins - Danilo Garofalo; Marcos Ferreira (European Journal of Geography)
One of the main problems associated with the analysis of water quality parameters (WQPs) in developing countries is the low number of sampling sites in small watersheds. One of the strategies used to solve this problem involves estimating WQPs based on the extrapolation of measurements carried out in other basins using regionalization methods associated with landscape characteristics. The objectives of this study were to evaluate the associations between landscape characteristics and WQPs and to propose a methodology for the regionalization of WQPs based on landscape characteristic data obtained from basins where WQP data were sampled. The study area was the upper Piracicaba-Jaguari River basin located in south-western Brazil. The methodology was based on a survey of 27 environmental variables and 12 water quality parameters in 44 small sub-basins. The non-parametric k-nearest neighbour regression (K-NNR) algorithm was used to estimate the WQP values for the small sub-basins that lacked data. The results showed that the landscape characteristics of the studied sub-basins related to land use and cover significantly influenced the WQPs. The mapped regions showed significant differences among the total dissolved solids, chloride, electric conductivity, pH, salinity, resistivity, dissolved oxygen, and nitrate parameter values.